IDDF2018-ABS-0120 The effect of OMEGA-3 fatty acid supplementation on paediatric non-alcoholic fatty liver disease: a meta-analysis of randomised controlled trials. (June 2018) - Wong, Martin MH; Lo, Kenneth; Tam, Wilson
Abstract : Background: Paediatric non-alcoholic fatty liver disease (NAFLD) is an obesity-related disease with growing prevalence worldwide. While current guidelines recommend lifestyle modification, omega-3 supplementation has been suggested as an emerging therapeutic option. Despite supporting evidence demonstrated among adult NAFLD patients, similar meta-analysis among the paediatric population is lacking. The present review aimed to evaluate the efficacy of omega-3 supplementation among children with NAFLD. Methods: A systematic review of all randomised controlled trials (RCT) on NAFLD patients aged 18 or under was conducted using 16 multiple databases including Medline, EMBASE and Cochrane Central Register of Controlled Trials. PRISMA guideline was followed. The search was conducted by two independent reviewers, with discrepancies resolved by the third reviewer. Outcomes were categorised into anthropometric (e.g. body mass index), cardio-metabolic (e.g. triglycerides and insulin resistance) and hepatic outcomes (e.g. liver enzymes). Using mean differences (MD), meta-analysis was conducted on outcomes reported in more than one study using a random-effect model. If only median and inter-quartile ranges were provided, they were transformed into mean and standard deviation before meta-analysis. Heterogeneity was examined using I 2 statistics. The Cochrane Collaboration's tool for assessing the risk of bias was used to examine the quality of the included studies. Results: After screening 2962 papers, six papers with 326 subjects from five RCT were included in the present review. The included studies were conducted in Canada, Italy, Poland and Turkey. Omega-3 supplementation significantly increased body mass index z-score (MD=0.09), reduced the levels of serum triglycerides (MD=−9.52) and alanine aminotransferase (ALT) (MD=−12.04), and improved insulin sensitivity (MD of the homeostasis model assessment of insulin resistance=−0.49). Heterogeneity was low (below 30%) across various outcomes, and the study quality was generally high, with three papers having low risks of bias in all six domains. Conclusions: To conclude, omega-3 supplementation reduced serum triglycerides and ALT, and improved insulin sensitivity among children with NAFLD. It may act as a potential supplementation for paediatric NAFLD patients. But more trials should be conducted, particularly in Asian regions.